Distortions in world trade: Recent developments - Hans Joachim Hochstrate; Ralf Zeppernick (Intereconomics, 1988)
The functioning of the world trading system is seriously distorted by a multitude of protectionist measures that impede a possible expansion in world trade and national product. Hans Joachim Hochstrate and Ralf Zeppernick analyse the latest developments against the background of the current Uruguay Round of GATT negotiations.
Keywords: 330; GATT